Analisis Pengaruh Tingkat Partisipasi Angkatan Kerja, Indeks Pembangunan Manusia dan Kemiskinan Terhadap Pertumbuhan Ekonomi Provinsi Papua Barat Tahun 2014-2022 - Muhammad Akbar Asyari; Maryana Ulfa; Omen Omen; Muhammad Kurniawan (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
Economic growth is essentially the most important aspect in a country. An increase in the quality of life of the community that occurs in an area can mean that the area has continued economic growth. Economic growth can be reflected in changes in GRDP in a region. This research uses eviews analysis 10. Labor Force Participation Rate (TPAK), human development index and poverty are among the Human Resource factors that contribute to the formation of Gross Regional Domestic Product (GRDP) which can encourage Economic growth of a region. The aim of this research is to find out the influence of the level of labor force participation and poverty as seen from the human development index on economic growth in the province of West Papua in 2014-2022. The data used in this research uses time series data for the period 2014-2022, using quantitative descriptive methods with the eviews 10 analysis tool. Independent variables consist of Labor Force Participation Rate (TPAK) as X1, human development index (HDI) as X2 and poverty (k) as X3 and Economic Growth as (Y). The results of this study show that TPAK, HDI and K simultaneously have a positive and insignificant effect.